2014
DOI: 10.1021/sc500181z
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesized Bimetallic Au–Pd Nanoparticles Supported on TiO2 for Solvent-Free Oxidation of Benzyl Alcohol

Abstract: A green bioreductive approach with Cacumen Platycladi (CP) extract was adopted to fabricate bimetallic Au− Pd/TiO 2 catalysts for solvent-free oxidation of benzyl alcohol (BzOH) to benzaldehyde (BzH) with molar oxygen at atmospheric pressure. The Au−Pd nanoparticles (NPs) before being immobilized onto TiO 2 were determined by transmission electron microscopy. And, the catalysts were further analyzed by X-ray diffraction, X-ray photoelectron spectroscopy, thermogravimetric analysis, etc. Effects of Au/Pd molar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(70 citation statements)
references
References 50 publications
0
70
0
Order By: Relevance
“…The calcination temperature had great effect on the catalytic activity of the catalysts [62,63]. As shown in Fig.…”
Section: The Effect Of Different Calcination Temperature On Desulfurimentioning
confidence: 95%
“…The calcination temperature had great effect on the catalytic activity of the catalysts [62,63]. As shown in Fig.…”
Section: The Effect Of Different Calcination Temperature On Desulfurimentioning
confidence: 95%
“…Carbohydrates and organic acids, present in C. paradisi were believed to be responsible for the formation of nanoparticles [ 89 ]. Also, Hang et al reported bimetallic Au-Pd/TiO 2 catalysts for solvent-free oxidation of benzyl alcohol (BzOH) to benzaldehyde (BzH) with Cacumen platycladi ( CP ) extract [ 90 ]. With high BzOH conversion (~78 %) and selectivity (~96 %), recycling tests showed that even after seven recycles, the catalyst still remained suggesting excellent durability and reusability leading towards industrial application [ 90 ].…”
Section: Plant Derived Materialsmentioning
confidence: 99%
“…Specifically, bioreduction method using plant biomass and microorganism has been developed to prepare Ag NPs as it is an environmentally benign and reliable approach to stable metal NPs [22]. Compared with microorganism-mediated bioreduction, the plant-mediated ones can circumvent the laborious cultivation of microorganisms and they possess higher reaction rate [23][24][25][26] NPs by microwave-assisted bioreduction with Cissus quadrangularis extract [30].…”
Section: Introductionmentioning
confidence: 99%